Pemberdayaan Perempuan Pengrajin Kain Tenun Ikat Tanimbar di GPM Klasis Tanimbar Selatan - Mailuhuw, Lendy Florien; Malindar, Balthasar; Kelmaskosu, Brusly Watson; Lelloltery, Marco Franc (Sekolah Tinggi Teologi Sriwijaya, 2024)
Tanimbar Archipelago Regency is one of under-developed region and has the highest rank of poor people in Mollucas Province. Poverty reduction is not just the responsibility of the government, but it is also the responsibility of the church to empower the members of the congregation. One of the potential that exist in congregation is skill in making the woven fabric of Tanimbar and its modification products that can be developed for improve the welfare of congregation and society. This research aimed to discover the dynamic of the woven fabric business of the weaver women who are members of Mollucas Protestant Church in South Tanimbar Classist and how the empowering program that been done by the Church to empowered those weaver women. The method that has been used in this research was descriptive qualitative research. The data collection techniques of this research were observation, interview, and documentation. The result of this research revealed that the weaver women had developed their creations by making the woven fabric of Tanimbar into many products. And those products have attracted customers even to foreign countries. The Mollucas Protesntant Church has empowered the weaver woman by giving the workshop and fund giving. However, the empowering program has not given maximum impact. They are still facing a lot of struggles and obstacles in expanding their business. So, this research recommended that the Mollucas Protestant Church in South Tanimbar Classist should improve the empowering program in porivision of capital and entreprenuership workshop for the weaver woman.